Identification of C5+ extraband of butyrylcholinesterase and two protein bands cathodic to it (Medical Journal of Indonesia, 2001)
Electrophoresis of human plasma yields 4 butyrylcholinesterase (BChE) protein bands, i.e. C1, C2, C3, C4 and in some individuals also an extraband C5+. In addition to that other protein bands called "S" bands are also invariably detected. In order to know whether the C5+ and the "S" bands are related to the BChE protein, we have carried out immunological and peptide mapping studies on these proteins. The immunology approach was done by raising polyclonal antibodies against each protein bands (S1, S2, C4 and C5+) and reacted to the plasma protein bands transferred on nitrocellulose papers. Individual raised antibodies recognized all protein bands studied including the C4, an isozyme of BChE, indicating that the protein bands contain similar epitopes. Several protein bands cathodic to S1 also reacted with the antibodies, suggesting that they are probably fractions of the BChE protein, as well. When individual protein bands were digested with S. aureus V8 toxin and α-chymotrypsin, they revealed a striking similarity in peptide pattern among each other. These studies indicate that the S1, S2 and C5+ protein bands belong to the BChE protein. (Med J Indones 2001; 10: 144-9) Keywords: , ,